1989
DOI: 10.1177/002246698902300109
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputer Implementation In Secondary Special Education Programs: A Study Of Special Educators; Mildly Handicapped Adolescents; And Administrators' Perspectives

Abstract: The purpose of this study was to examine the implementation and utilization of microcomputers in secondary special education programs. Twenty-two high school special education teachers, 24 mildly handicapped adolescents, and 8 administrators from six high schools in an urban school district were interviewed. Results indicated that, despite the district's considerable investment in hardware, software, and technical assistance, almost half of the teachers were not using microcomputers. Teachers who had at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Other promising ideas include the use of remedial programs, including before and after-school tutoring (peer and adult-mediated), parent training, and services to help students find and maintain jobs during the summer months (e.g., school-based job clubs). Finally, districts would pursue inservice or related training options for teachers in such areas as content organizers (see Derr & Peters, 1986), team-teaching techniques, interagency collaboration (see Kortering & Edgar, 1988;Rusch & Phelps, 1987;Szymanski & King, 1989;Szymanski, Hanley-Maxwell, & Asselin, 1990) and computer-assisted instruction (see Okolo, Rieth, & Bahr, 1989;Woodward, Carnine, & Collins, 1988).…”
Section: Preparing Youth For Utilitarian Rolesmentioning
confidence: 99%
“…Other promising ideas include the use of remedial programs, including before and after-school tutoring (peer and adult-mediated), parent training, and services to help students find and maintain jobs during the summer months (e.g., school-based job clubs). Finally, districts would pursue inservice or related training options for teachers in such areas as content organizers (see Derr & Peters, 1986), team-teaching techniques, interagency collaboration (see Kortering & Edgar, 1988;Rusch & Phelps, 1987;Szymanski & King, 1989;Szymanski, Hanley-Maxwell, & Asselin, 1990) and computer-assisted instruction (see Okolo, Rieth, & Bahr, 1989;Woodward, Carnine, & Collins, 1988).…”
Section: Preparing Youth For Utilitarian Rolesmentioning
confidence: 99%
“…In a study of the implementation of computers in secondary special education programs, a sample of 22 high school special education teachers, 24 mildly handicapped adolescents, and 8 special education administrators from six high schools were interviewed concerning perceived benefits, barriers, and activities related to computer uses in the schools (Okolo et al, 1989). In a disturbing revelation, although all but one of the teachers reported easy access to microcomputers, almost half of the group had not used them over the past year.…”
Section: The Computer Locationmentioning
confidence: 99%
“…In the Okolo study (Okolo et al, 1989), teachers identified the computer's ability to support and supplement instruction as the most important benefit offered by computer use. Other responses were that microcomputers facilitated the individualization of instruction and that microcomputers added variety to classroom activities and thus made teaching more interesting.…”
Section: Usage Patternsmentioning
confidence: 99%
See 2 more Smart Citations